Gastrointestinal disease: An endoscopic approach: Vol.2 (Blackwell Science, 1997)
The book provides the current status of gastrointestinal endoscopy with continual imaging, therapeutic modilities, and clinical investigator initiatives. The state of the art as provoded in this book brings forward the very best clinicians in the field to discuss endoscopy with objectivity and enthusiasm. In this era of cost containment and managed care, the ability to deliver efficacious care with the least invasive method is critical to effective patient management. Endoscopic techniques, in many cases, are the most cost effective management option. The book presents the entire field with all of its advancements and future potential